Oxidative Stress in Pulmonary Fibrosis: A Possible Role for Redox Modulatory Therapy - Kinnula, Vuokko L. (American Thoracic Society, 2005)
Idiopathic ulmonary fibrosis (histopathology of usual interstitial pneumonia) is a progressive lung disease of unknown etiology. No treatment has been shown to improve the prognosis of the patients with this disease. Recent evidence, including the observations that the patients with idiopathic pulmonary fibrosis have higher levels of oxidant stress than control patients, and a recent multicenter European study examining the effect of the antioxidant N-acetylcysteine on the progression of idiopathic pulmonary fibrosis suggest that the cellular redox state may play a significant role in the progression of this disease. These complex mechanisms include activation of growth factors as well as regulation of matrix metalloproteinases and protease inhibitors. Potential future approaches for the therapy of interstitial pulmonary fibrosis may involve synthetic agents able to modulate cellular redox state. Investigation into therapeutic approaches to inhibit oxidant-mediated reactions in the initiation and progression of pulmonary fibrosis may provide hope for the future treatment of this disease.